Preparing for the future: The OECD-countries in comparison - Horst Hanusch; Yasushi Hara (Universität Augsburg, Institut für Volkswirtschaftslehre, 2016)
In modern growth or development theory innovation is a crucial factor which pushes the dynamics of an economy and determines its success in the future. Out of innovations, created in the presence, the potentials for the future of a country are prepared, deciding how its economic fitness and competitiveness will emerge. So, future-orientation is in a natural way connected with innovativeness of a firm, a region or a country and shapes the strength and the specifics of the process of development. Looking around the world economy, one can observe a variety of countries which exist at different levels of development. Each of them has to master its economic future, choosing an own specific development strategy. How the various countries, belonging to different continents and cultures, will succeed in this endeavor is surely one of the most exciting and important issues of coming decades. In this global context our study is focusing on "future preparedness" of a specific group of countries, the so called OECD- countries. The origin of this group dates back to 1960, when 18 European countries and the United States as well as Canada created in Paris an organization dedicated to global development. Today the group consists of 34 member countries which span the globe from North to South America, to Europe and the Asia-Pacific region. They include many of the world's most advanced countries but also emerging ones like Mexico, Chile and Turkey. The concept of "future preparedness" gets its analytical and empirical relevance when it is placed and investigated within a specific development model. Such a model determines the theoretical basis of the study and provides the necessary ingredients for an empirical application. In our study we will use "Comprehensive Neo-Schumpeterian Economics" (CNSE) as an analytical framework (Hanusch and Pyka, 2007). This approach is based (a) 2 on the notion of future-orientation penetrating all spheres of socio-economic life in developed as well as in developing countries; (b) on the principle of innovation as the main driving force and the engine of future-orientation and development. Based on the concept of CNSE the central aim of our study is to gain new insights and findings concerning the "future preparedness" of the OECD-countries. To meet this target we (a) rely on the notion of "future-orientation" as a basic prerequisite for being prepared to master the future; (b) try to bring this concept of "future preparedness" on a concrete basis by using indicator analysis embedded in the framework of CNSE; (c) investigate patterns of similarities in the set of indicators; (d) show how these patterns look like by applying cluster analysis; (e) draw some conclusions from the patterns concerning the status and variety of future-orientation in the group of OECD-countries. Future-orientation will be described and characterized in total by 45 indicators, focusing on the real (16), the public (21) and the financial sector (08) of an economy. The indicators reflect many different activities in the various countries related to innovation and the "emerging future" within the concept of CNSE. Dependent on data availability, the indicator sets comprise different years mainly in the period between 2006 and 2012.
urn:nbn:de:bvb:384-opus4-710760
Keywords: N10; P00; O10; 330; Development Models; Neo-Schumpeterian Economics; Indicator Analysis; Future-Oriented Country Analysis (FCA)